2011
DOI: 10.1103/physrevb.83.024512
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and superconducting properties of the fully gapped noncentrosymmetric 5d-electron superconductors CaMSi3

Abstract: We report crystallographic, specific heat, transport, and magnetic properties of the recently discovered noncentrosymmetric 5d -electron superconductors CaIrSi3 (Tc = 3.6 K) and CaPtSi3 (Tc = 2.3 K). The specific heat suggests that these superconductors are fully gapped. The upper critical fields are less than 1 T, consistent with limitation by conventional orbital depairing. High, non-Pauli-limited µ0Hc2 values, often taken as a key signature of novel noncentrosymmetric physics, are not observed in these mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 29 publications
21
61
1
Order By: Relevance
“…The calculated equilibrium lattice parameters (a and c), the volume of primitive unit cell (V ), internal parameters (z Ir , z Si1 and z Si2 ), bulk modulus (B) and its pressure derivative (B ′ ) with and without SOI are presented in Tab. 1, together with previous theoretical [23,24] and experimental [18,21] results for comparison. As can be seen from this table, the effect of SOI on the structural properties of CaIrSi 3 is very small.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated equilibrium lattice parameters (a and c), the volume of primitive unit cell (V ), internal parameters (z Ir , z Si1 and z Si2 ), bulk modulus (B) and its pressure derivative (B ′ ) with and without SOI are presented in Tab. 1, together with previous theoretical [23,24] and experimental [18,21] results for comparison. As can be seen from this table, the effect of SOI on the structural properties of CaIrSi 3 is very small.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 99%
“…In particular, Smidman and co-workers [16] report magnetic susceptibility, specific-heat, and muon spin rotation/relaxation (µSR) measurements on LaPtSi 3 and LaPdSi 3 and conclude that LaPtSi 3 is a type-II superconductor with T c = 1.52 K, whereas LaPdSi 3 is a type-I superconductor with T c = 2.65 K. Furthermore, the synthesis of nine new noncentrosymmetric ternary silicide superconductors, including CaIrSi 3 (T c = 3.6 K), by arc melting has been reported [17]. Following this experimental work [17], Eguchi and co-workers [18,19] have shown that CaIrSi 3 is nonmagnetic, fully gapped superconductor based on studies with polycrystalline samples. Thus, in contrast to the cerium-based NCS, no magnetic order exists to possibly weaken or interfere with the superconducting state.…”
Section: Introductionmentioning
confidence: 99%
“…After subtracting σ nm from σ to give σ sc as described above, λ can be calculated at each temperature, with a correction for the strong field dependence of the depolarization rates made using the B c2 (T ) data from Ref. [35] and Eq. 4.…”
Section: B Transverse-field Muon-spin Rotationmentioning
confidence: 99%
“…CaIrSi 3 and CaPtSi 3 are NCS with superconducting transition temperatures of 3.6 and 2.3 K respectively and therefore do not require pressure to induce the superconducting state unlike their Ce analogues 35,36 . Specific heat data are in general agreement with these superconductors being fully gapped, however, CaIrSi 3 appears to show a deviation from a pure s-wave gap, which has been suggested as evidence for a multiband or anisotropic gap 35 . In the presence of Ir and Pt it is expected that spin-orbit coupling will be significant, strengthening the possibility that the mechanisms for superconductivity might not be entirely conventional in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Ce materials are antiferromagnetic and become superconducting only under pressure. However, in materials such as BaPtSi 3 [17], LaRhSi 3 [18], CaPtSi 3 [19,20], CaIrSi 3 [19,20], LaPtSi 3 [21], and LaPdSi 3 [21], which also adopt the body-centered tetragonal BaNiSn 3 -type structure but do not show strong electronic correlations, superconductivity with the BCS characteristics has been discovered at ambient pressure.…”
Section: Introductionmentioning
confidence: 99%